Para além do ilustrativo : letramentos visuais em práticas de educação linguística - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
In the contemporary world, it is essential that educational practices consider the multiplicity of languages present in various spheres, including the multimodality of texts, as well as the diverse semiotics characteristic of the digital environment, such as images. In this direction, language education must promote visual and critical literacies, so that students can expand their processes of meaning construction in language classes. In view of these issues, this study aims to analyze how the frequent use of digital information and communication technologies (ICTs) in remote teaching promoted meaningful experiences of visual and critical literacy in language education. To do so, the specific objectives were: (i) to reflect on the various forms of language, beyond writing and orality, present in our society and their implications for language education; (ii) to analyze teachers' perceptions regarding the use of visual literacy in language education; (iii) to investigate the functions that images played in the construction of meaning in virtual English language classes. The study adopted a qualitative, interpretative approach, in which researchers, as social agents, attribute meanings to the research, according to Moita Lopes (2006). The participants were nine English language teachers who work at different educational levels, from basic to postgraduate. The ongoing analysis points to the need for teachers to have training in which they experience new ways of learning and teaching. In addition, it also highlights the need for investment so that schools can promote greater access to the digital world.
Beyond the illustrative: visual literacies in linguistic education practices
Keywords: Multimodalidade; Letramentos visuais; Educação linguística; Multimodality; Visual literacy; Language education; LINGUISTICA::LINGUISTICA APLICADA